Pengaruh Lingkungan Kerja, Kompensasi Dan Kepuasan Kerja Terhadap Motivasi Intrinsik Pegawai, di Kantor Kelurahan Purwokinanti Berlian - Lero, Stevani; Subiyanto, Didik; Yulianto, Eko (Gorontalo State University, 2026)
This istudy iaims ito ianalyze ithe iinfluence iof ithe iwork ienvironment, icompensation, iandjobsatisfaction ion ithe iintrinsic imotivation iof iemployees iin iPurwokinanti iBerlian iVillage.Data iwere icollected ithrough iquestionnaires ifrom i60 iemployees iand ianalyzed iusing iSPSS25. iThe iresults ishowed ia ipositive iand isignificant iinfluence ion iintrinsic imotivation, iwhile the iwork ienvironment, icompensation, iand ijob isatisfaction ihad ia ipositive ieffect ion intrinsic imotivationThis istudy iaims ito ianalyze ithe iinfluence iof ithe iwork ienvironment, icompensation, iandjobsatisfaction ion ithe iintrinsic imotivation iof iemployees iin iPurwokinanti iBerlian iVillage.Data iwere icollected ithrough iquestionnaires ifrom i60 iemployees iand ianalyzed iusing iSPSS25. iThe iresults ishowed ia ipositive iand isignificant iinfluence ion iintrinsic imotivation, iwhile the iwork ienvironment, icompensation, iand ijob isatisfaction ihad ia ipositive ieffect ion intrinsic imotivation.